2012
DOI: 10.1038/labinvest.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin-1 is a ‘nuclear'-negative acute-phase protein in rat liver: a comparison with other iron-transport proteins

Abstract: Liver is the central organ of iron metabolism. During acute-phase-response (APR), serum iron concentration rapidly decreases. The current study aimed to compare expression and localization of iron transport protein ferroportin-1 (Fpn-1) and of other iron import proteins after experimental tissue damage induced by injecting turpentine oil in the hind limbs of rats and mice. Serum and spleen iron concentration decreased with an increase in total liver, cytoplasmic and nuclear iron concentration. In liver, mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…However, independent of post-translational regulation, our data show that IL-6 reduces Fpn1 mRNA. These results are consistent with published data, which demonstrated that IL-6 is able to downregulate Fpn1 levels in the HepG2 cell line [48] and upregulate the mRNA level of sCp [46, 47]. We demonstrate that the GPI-Cp isoform is also upregulated and the protein level of the two isoforms follow the same behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…However, independent of post-translational regulation, our data show that IL-6 reduces Fpn1 mRNA. These results are consistent with published data, which demonstrated that IL-6 is able to downregulate Fpn1 levels in the HepG2 cell line [48] and upregulate the mRNA level of sCp [46, 47]. We demonstrate that the GPI-Cp isoform is also upregulated and the protein level of the two isoforms follow the same behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Also, in vitro hepatocytes treated with interleukin-6 reduced liver ferroportin by 90% at 24 hours. 11 In this study, daily propranolol use following LCHS and LCHS/CS significantly improved liver ferroportin expression. Ferroportin expression is impacted by inflammatory states such as severe trauma and chronic stress as well as hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 52%
“…Seven days following LCHS and LCHS/CS, liver ferroportin expression was decreased and this finding correlated with decreased iron levels after trauma. 12 Similarly, Naz et al 11 demonstrated a 30–50% decrease in liver ferroportin expression at 24 hours in a rodent model of tissue injury. Also, in vitro hepatocytes treated with interleukin-6 reduced liver ferroportin by 90% at 24 hours.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations